The Threat of Syncretism to Ezekiel's Exilic Audience in the Dry Bones Passage - Launderville, Dale (2015)
The divine functions of infusing humans with knowledge and life through linguistic and material media are integral to Ezekiel's vision of the dry bones (Ezek 37:1-14). This article brings together and interprets Akkadian texts of diverse genres that show that such functions were also carried out by the Mesopotamian deities Ištar/Inana and Ea/Enki and thus proposes that the threat of syncretism was high. Some of the ways the Mesopotamian deities carry out such functions may seem to be more inclusive of aspects of human experience shortchanged (e.g., feminine agency) by Yahwism. Ezekiel's refusal to acknowledge the reality of other deities shapes his worldview and marks a non-negotiable starting point for perceiving the distinctiveness of Yhwh. The concrete engagement of the exiles in "knowing" Yhwh is the recontextualization necessary for the dislocated exiles to avoid syncretism.